2022
DOI: 10.3390/rs14133020
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Levels of Soil Salination and Alkalization by Integrating Machining Learning Methods and Soil-Forming Factors

Abstract: Accurate updating of soil salination and alkalization maps based on remote sensing images and machining learning methods plays an essential role in food security, biodiversity, and desertification. However, there is still a lack of research on using machine learning, especially one-dimensional convolutional neural networks (CNN)s, and soil-forming factors to classify the salinization and alkalization degree. As a case study, the study estimated the soil salination and alkalization by Random forests (RF) and CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Overall, the RF model performed the best [23]. Convolutional Neural Network (CNN) and RF models were compared for soil salinity estimates across China and the results showed that the RF model was the most reliable [24]. In another study comparing the SVM, ANN and RF models to retrieve soil salinity estimates from Sentinel-2 images across Chinese arid areas, the SVM model reached the highest accuracy [10].…”
Section: Which Machine-learning Model Performs Best?mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the RF model performed the best [23]. Convolutional Neural Network (CNN) and RF models were compared for soil salinity estimates across China and the results showed that the RF model was the most reliable [24]. In another study comparing the SVM, ANN and RF models to retrieve soil salinity estimates from Sentinel-2 images across Chinese arid areas, the SVM model reached the highest accuracy [10].…”
Section: Which Machine-learning Model Performs Best?mentioning
confidence: 99%
“…As soil salinity field measurements are costly and time consuming, most of the studies investigating machine-learning potential for soil salinity mapping relied on training sets gathering less than 100 samples [21,[23][24][25]28,29]. In this context, it is crucial to increase the training set size in order to improve the reliability of machine-learning models to estimate soil salinity.…”
Section: Machine-learning Training Set Weaknessmentioning
confidence: 99%
“…One of the primary challenges is the limited spatial coverage. As most sensors have low spatial coverage, this has restricted soil salinization studies mainly to a local scale [151].…”
Section: Challenges In Salinization Mappingmentioning
confidence: 99%
“…For this reason, the use of RS as a rapid, non-contact, and low-cost technique was shown to be valuable for detecting SSS either directly on bare soils with efflorescence and white-crust or indirectly on covered soils through the biophysical characteristics of vegetation or soil moisture [4,20,21]. Some indirect environmental factors, such as terrain, hydrology, climate, and the like, could also be incorporated to characterize soil salinity [22][23][24][25], as they are mutually associated with one another. The commonly used RS inversion method is to choose a significant band or combine some sensitive bands to form different kinds of salinity indices to invert soil salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Multispectral satellite images (such as MODIS, Landsat, and Sentinel) are frequently used because the multi bands of visible spectra (0.38~0.76 µm) and near-infrared spectra (0.76~3 µm) can provide the highest separability between salinized and non-salinized soils for distinguishing saline-alkaline soil regions [11,[26][27][28][29][30][31]. The Sentinel-2 multispectral sensor has a higher spatial resolution (10 m) in the red, green, blue, and near-infrared spectrum than MODIS or Landsat, in which the bands can be combined in different ways to obtain various salinity indices to invert SSS [24]. Overall, previous studies using RS mainly focused on SSS mapping, while saline-alkaline problems have extended far beyond surface soils and also affect deep soils.…”
Section: Introductionmentioning
confidence: 99%